Peran Hukum Lingkungan dalam Mencegah Kerusakan dan Pencemaran Lingkungan Hidup pada Kasus Petambak Udang Ilegal di Kawasan Taman Nasional Karimun Jawa - Fernando Fernando; Syamsul Syamsul; Serlika Aprita (Lembaga Pengembangan Kinerja Dosen, 2024)
This research discusses the role of environmental law in preventing environmental damage and pollution with a case study of illegal shrimp farmers in the Karimunjawa National Park Area. The Karimun Jawa National Park area is an ecosystem that is rich in biodiversity and has vital ecological functions. However, illegal shrimp farming activities in this area have caused significant environmental damage, including decreased water quality and damage to mangrove habitats.This research uses a normative juridical approach to analyze applicable environmental legal regulations and policies as well as the effectiveness of law enforcement in preventing and dealing with the activities of illegal shrimp farmers. The research results show that although there are clear regulations regarding environmental protection, implementation and enforcement of the law are still weak. Lack of coordination between institutions, minimal human resources, and technical obstacles in the field are the main inhibiting factors in enforcing environmental law. This research recommends increasing law enforcement capacity, increasing coordination between institutions, and strengthening local community participation in environmental protection efforts in the Karimunjawa National Park Area. With these steps, it is hoped that environmental damage and pollution due to illegal activities can be minimized.